Morality, competition, and the firm : the market failures approach to business ethics - Heath, Joseph, 1967- (Oxford University Press, USA, 2014)
"In this collection of provocative essays, Joseph Heath provides a compelling new framework for thinking about the moral obligations that private actors in a market economy have toward each other and to society. In a sharp break with traditional approaches to business ethics, Heath argues that the basic principles of corporate social responsibility are already implicit in the institutional norms that structure both marketplace competition and the modern business corporation. In four new and nine previously published essays, Heath articulates the foundations of a "market failures" approach to business ethics. Rather than bringing moral concerns to bear upon economic activity as a set of foreign or externally imposed constraints, this approach seeks to articulate a robust conception of business ethics derived solely from the basic normative justification for capitalism. The result is a unified theory of business ethics, corporate law, economic regulation, and the welfare state, which offers a reconstruction of the central normative preoccupations in each area that is consistent across all four domains. Beyond the core theory, Heath offers new insights on a wide range of topics in economics and philosophy, from agency theory and risk management to social cooperation and the transaction cost theory of the firm"--